La Innovación Digital y su incidencia en la comercialización de las Agencias de Viajes de la ciudad de Loja. - Armijos Salinas, Gabriela Salome (2023)
This research has been developed to design a digital business model for the commercialization of touristic products and services for travel agencies in the city of Loja. The specialization of tourism in the city of Loja is considered vulnerable, especially in regards to travel agencies who provide advice and information about destinations in order to generate loyalty and satisfaction of demand, which directly affects the sales of touristic packages that are marketed by the travel agencies in the city. Furthermore, in the present investigation, the descriptive method was used to know the current situation of the digital media used in their tourist companies, which were the object of study. Similarly, the analytical method was used to obtain data about the perspective of the clients and/or visitors of the city of Loja about the distribution channels used by tourist companies. For this latter purpose a field investigation was carried out, with the use of tools such as surveys addressed to potential clients and / or visitors to the city of Loja, and interviews with representatives of travel agencies under a mixed approach of quantitative and qualitative information, which allowed visualizing the use that travel agencies give to digital media, as well as the lack of knowledge that visitors and potential customers have about these media. Using the information obtained from the representatives of the travel agencies, and potential clients, through the Canvas methodology, the strategies for the proposed business model were established, for which the following elements are determined; customer segment, value proposition, customer relationship, distribution channels, partners, key activities and resources, revenue structure and cost structure, in order to improve the marketing processes of travel agencies. Finally, it is concluded that innovation and the use of digital tools as means of dissemination and marketing of tourist services and products currently constitute a competitive advantage in relation to the desired results by travel agencies.